Toxicology and Biocompatibility of Nanomaterials - Weiss, Carsten; Diabaté, Silvia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book entitled "Toxicology and Biocompatibility of Nanomaterials" covers some recent insights into adverse but beneficial effects of nanomaterials on human health and the environment. Renowned experts in the field contributed to this Special Issue to make this an interesting read for both scholars and students.